2003
DOI: 10.1088/0957-4484/14/12/002
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of amorphous thin films deposited by de-focused pulsed laser ablation

Abstract: Amorphous thin films of composition Fe67Co18Si1B14 have been deposited onto glass substrates by KrF excimer laser ablation operating with 30 ns pulses at a repetition rate of 11 Hz and using a METGLAS2605CO® target as a function of the degree of focusing of the beam. We were able to deposit thin films and to prepare very soft magnetic amorphous thin films with a coercivity of about 400 A m−1. This level of magnetic softness is appropriate for different technological applications of amorphous thin films. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The fundamental features deriving from the peculiar production conditions are presented in comparison with previous results reported in the literature [8][9][10][11][12][13][14][15]. In particular, the role of the film nanogranularity is pointed out together with the observation of an amorphous structure of the terfenol-D films, as opposed to the crystalline one produced by standard nanosecond PLD.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…The fundamental features deriving from the peculiar production conditions are presented in comparison with previous results reported in the literature [8][9][10][11][12][13][14][15]. In particular, the role of the film nanogranularity is pointed out together with the observation of an amorphous structure of the terfenol-D films, as opposed to the crystalline one produced by standard nanosecond PLD.…”
Section: Introductionmentioning
confidence: 60%
“…particular, it was observed that pulsed laser deposition (PLD) preserves the original target stoichiometry strongly reducing the inclusion of impurities [8,9]. Moreover, the PLD technique with nanosecond laser pulses was successfully applied to produce films of TbDyFe [10][11][12] and other magnetoelastic materials [13,14]. More recently, multilayer films consisting of terfenol layers alternating with soft magnetic layers (Fe, FeCo) were produced in order to realize high magnetostriction films with low excitation magnetic fields, working on a basic idea somewhat similar to that of the spring magnets [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Aiming at modifying the structured geometries, the controlled laser defocusing technique was used. This technique has been successfully employed for different nanostructuring applications and allows to position the sample at different regions of the Gaussian beam distribution and this way to modify the machined area [38][39][40]. Therefore, the focusing point was displaced yielding different values of the spot diameter (ωz) and consequently different machined line-widths [41].…”
Section: Fabrication Of the Biomimetic Hierarchical Surface Micropatt...mentioning
confidence: 99%
“…The processes of magnetic film growth are sensitive to small changes in the deposition parameters, which makes it possible to control the magnetic properties in a wide range [6]. The mutual relationship between the static magnetic parameters and the microstructure of the cobalt films has been investigated in detail.…”
Section: Introductionmentioning
confidence: 99%